ANALYSIS OF HEMODIALYSIS SERVICE UTILIZATION BY JKN PARTICIPANTS IN THE SPECIAL REGION OF YOGYAKARTA: AN ANALYSIS OF BPJS KESEHATAN CLAIM DATA IN 2023 - Intan Corina Indra; Pujiyanto Pujiyanto; Fahdrian Kemala (Pusat Publikasi Nusantara, 2025)
Chronic kidney disease (CKD) has become a serious global health problem with significant socio-economic implications. This study aims to analyze the determinants of the utilization of hemodialysis services for National Health Insurance (JKN) participants in the Special Region of Yogyakarta (DIY) in 2023. The study employs a cross-sectional design to analyze secondary data from the BPJS Kesehatan claim database in 2020, focusing on JKN participants receiving dialysis services at Advanced Referral Health Facilities (FKRTL). Data extraction is followed by analysis using STATA software, which includes univariate and bivariate analyses, multicollinearity and overdispersion tests, model comparison via Akaike Information Criterion (AIC), and multivariate analysis through Poisson regression and Binomial Negative methods. A total of 3,220 participants (0.089%) were enrolled in the study. The highest distribution of participants was in Sleman Regency (36.49%), followed by Bantul (29.53%), and Yogya City (25.96%). From the results of the binomial regression analysis, it was found that the age factor had a significant negative influence (p=0.000) with a coefficient of -0.0046 and an IRR of 0.9954, which means that every increase in age by one year will decrease the frequency of visits by 0.46%. The prevalence of diabetes (3.1%) and hypertension (10.2%) which exceed the national average indicates a high risk factor for CKD in this region is high. The age factor and location of health facilities in SLEMAN Regency significantly affected the frequency, while the segment group, gender, and nursing class rights did not show significant influence.